Culturally Responsive Writing Instruction for Secondary Students With Emotional and Behavioral Disorders. (April 2017) - Lewis Chiu, Calli; Carrero, Kelly M.; Lusk, Mandy E.
Research suggests that teachers often do not adequately prepare students with emotional and behavioral disorders (EBD) to utilize organizational structures and basic writing skills that are necessary to produce cohesive essays. Among the challenges of effectively teaching writing to secondary students with EBD is how to deliver culturally responsive instruction to students who come from a variety of different backgrounds. This article presents specific strategies for infusing culturally responsive practices into scaffolded instruction for teaching written expression to youth with EBD.